In Vivo Antiplasmodial, Anti-Inflammatory, and Analgesic Properties, and Safety Profile of Root Extracts of Haematostaphis barteri Hook F. (Anacardiaceae) - Johnson Nyarko Boampong (Journal of Parasitology Research)
Malaria is an endemic disease globally and the conundrum of drug resistance has led to the search for newer antimalarial agents. The root extract of H. barteri was evaluated for antimalarial, analgesic, and anti-inflammatory properties. The prophylactic effect of H. barteri on P. berghei was determined by pretreating mice with aqueous root extract of H. barteri (30–300 mg/kg), saline, and 1.2 mg/kg sulfadoxine/pyrimethamine for three days followed by 1 × 106 P. berghei inoculation. Parasite density was measured after 72 h. The curative antimalarial property of the extract was assessed by treating mice with extract, saline, and 1.14 : 6.9 mg/kg Artemether : Lumefantrine four days after 1 × 106 P. berghei inoculation. Selected organs were harvested for toxicity assessment. The anti-inflammatory and analgesic effect of the extract was determined in the carrageenan and thermal tail withdrawal tests, respectively. The extract significantly reduced the parasite density in the prophylactic but not the curative study. The anti-inflammatory and analgesic activities of the extract were significant (P<0.05) only at the highest doses employed. Regeneration of hepatocytes was also evident in the extract treated groups. The extract has prophylactic but not curative activity on P. berghei-induced malaria. The anti-inflammatory and analgesic property of the extract occurred at the highest doses used.